2020
DOI: 10.1093/ecco-jcc/jjaa161
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Management of Paediatric Crohn’s Disease: an ECCO-ESPGHAN Guideline Update

Abstract: Objective We aimed to provide an evidence-supported update of the ECCO-ESPGHAN guideline on the medical management of paediatric Crohn’s disease [CD]. Methods We formed 10 working groups and formulated 17 PICO-structured clinical questions [Patients, Intervention, Comparator, and Outcome]. A systematic literature search from January 1, 1991 to March 19, 2019 was conducted by a medical librarian using MEDLINE, EMBASE, and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
553
4
88

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 389 publications
(656 citation statements)
references
References 234 publications
11
553
4
88
Order By: Relevance
“…The low rate of steroid dependence and improvement of height z-scores for both steroid-and EEN-exposed cohorts suggest an adequate escalation of immune suppression to avoid repeated and prolonged steroid treatment (84% by year 2 in the steroid treatment group vs 51% in EEN-induction group, p = 0.02) This is in keeping with prospective pediatric evidence for the contribution of immunomodulators which is only available for reducing steroid exposure [1]. Scarpato et al also show that after longer follow-up, there is no difference in the subgroups requiring treatment escalation towards anti-tumor necrosis factor (anti-TNF) in the children diagnosed in the era 2003-2013.…”
supporting
confidence: 69%
See 4 more Smart Citations
“…The low rate of steroid dependence and improvement of height z-scores for both steroid-and EEN-exposed cohorts suggest an adequate escalation of immune suppression to avoid repeated and prolonged steroid treatment (84% by year 2 in the steroid treatment group vs 51% in EEN-induction group, p = 0.02) This is in keeping with prospective pediatric evidence for the contribution of immunomodulators which is only available for reducing steroid exposure [1]. Scarpato et al also show that after longer follow-up, there is no difference in the subgroups requiring treatment escalation towards anti-tumor necrosis factor (anti-TNF) in the children diagnosed in the era 2003-2013.…”
supporting
confidence: 69%
“…The authors showed that these low trough doses were associated with a higher chance to develop antibodies to infliximab (ATI), which was reduced by co-immunomodulators. The trough levels themselves were not associated with age or co-immunomodulation, suggesting that optimized dosing for patients with higher clearance is achievable and recommendable [1]. Toxicity of higher trough levels has not been shown to date, whereas higher trough levels are associated with improved mucosal healing and outcomes of perianal disease [17,18].…”
mentioning
confidence: 96%
See 3 more Smart Citations